2023
DOI: 10.3201/eid2904.221628
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Temporal Changes in SARS-CoV-2 Spike Antibody Levels and Variant-Specific Risk for Infection, Dominican Republic, March 2021–August 2022

Abstract: G iven widespread unreported SARS-CoV-2 infections, variable immunologic response based on host immunogenicity, vaccine type, viral strain, timing and sequence of vaccine or viral exposure, and humoral waning, the global SARS-CoV-2 immune landscape is largely unknown. Most countries launched national COVID-19 vaccination campaigns during early 2021, but few studies have characterized population-level immunologic responses to SARS-CoV-2, and fewer have aimed to translate findings to immunologic protection. Many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…We previously reported on an independent cohort of patients presenting to health facilities in the Dominican Republic with undifferentiated febrile infection, and demonstrated similar normalization of population-level S-antibody titer distribution over time. 8 In South Africa, which has been heavily impacted by sequential waves of variant transmission, 13 a prospective serology-based cohort study documented similar trends before and after the Omicron BA.1 wave, with waning spike IgG antibody levels among individuals with high baseline antibody levels and boosting among individuals with lower baseline antibody levels. 14 Although we used a total S-antibody assay for our study, the underlying principle suggests that similar dynamics would be observed for any humoral marker that tracks with protection against infection.…”
Section: Discussionmentioning
confidence: 97%
“…We previously reported on an independent cohort of patients presenting to health facilities in the Dominican Republic with undifferentiated febrile infection, and demonstrated similar normalization of population-level S-antibody titer distribution over time. 8 In South Africa, which has been heavily impacted by sequential waves of variant transmission, 13 a prospective serology-based cohort study documented similar trends before and after the Omicron BA.1 wave, with waning spike IgG antibody levels among individuals with high baseline antibody levels and boosting among individuals with lower baseline antibody levels. 14 Although we used a total S-antibody assay for our study, the underlying principle suggests that similar dynamics would be observed for any humoral marker that tracks with protection against infection.…”
Section: Discussionmentioning
confidence: 97%
“…The time interval was defined as the period between the most recent administration of a COVID-19 vaccine or occurrence of a COVID-19 infection and the time of blood sampling. To investigate the temporal dynamics of antibody concentrations concerning the interval from antigen exposure to delivery, quadratic curves were plotted using a polynomial regression approach to address the non-linear temporal dynamics seen in previous clinical observations [ 29 , 30 ]. Patients infected within 7 days were excluded from the regression as the prior univariable analysis revealed no significant antibody differences.…”
Section: Methodsmentioning
confidence: 99%